Korelasi antara Monocyte Lymphocyte Ratio dengan Stadium Pasien Chronic Kidney Disease Non Hemodialisis di RSUD Dr. H. Abdul Moeloek Provinsi Lampung Tahun 2023-2024 - Ade Yonata; Dafa Rafiqi Akbar; Maya Ganda Ratna (Jurnal Kesehatan Amanah, 2024)
Chronic kidney disease (CKD) is a serious condition accompanied by various comorbidities, systemic inflammation, and kidney tissue damage, leading to a decline in the glomerular filtration rate (GFR), which determines CKD staging. The monocyte-lymphocyte ratio (MLR) can serve as a more practical alternative that does not increase laboratory examination costs and utilizes a complete blood count, a routine hospital test. Several studies have reported that MLR values are associated with clinical deterioration and inflammation in CKD patients. This study aims to determine the correlation between MLR and CKD stage in non-hemodialysis patients at Dr. H. Abdul Moeloek Regional General Hospital, Lampung. This study is an analytical observational study using a cross-sectional method involving all non-hemodialysis CKD patients who met the inclusion and exclusion criteria at Dr. H. Abdul Moeloek Regional General Hospital. The sampling technique used was total sampling, with a total of 346 non-hemodialysis CKD patients collected from medical records between July 2023 and June 2024. Data analysis was performed using the Spearman alternative test. Based on the study of 346 patients, bivariate analysis showed a significant correlation between MLR and CKD stage (p = 0.000; r = 0.444). There is a significant positive correlation of moderate strength between MLR and CKD stage in non-hemodialysis patients at Dr. H. Abdul Moeloek Regional General Hospital, Lampung.